2020
DOI: 10.1111/ajo.13262
|View full text |Cite
|
Sign up to set email alerts
|

Perineal trauma management and follow‐up: Are we meeting the standard of care?

Abstract: Background Birth‐related third‐ and fourth‐degree perineal trauma is common and associated with short‐ and long‐term complications. Aim To conduct a review of clinical audits investigating management of women with perineal trauma. Materials and Methods We identified all audits undertaken in eight New Zealand public hospitals between 2005 and 2014 that investigated whether women with birth‐related third‐ and fourth‐degree perineal trauma were receiving care according to clinical guidelines. We aggregated audit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The experience of childbirth has long been established to have a spectrum of potential impacts on the well-being of women, with potential negative impacts increasing clinical concern (Grandone et al, 2020;Harrison, Ayers, Quigley, Stein, & Alderdice, 2020;Peiris-John, Park, Wells, Kool, & Wise, 2020;Picetti et al, 2020;Watson, White, Hall, & Hewitt, 2020). Childbirth is a challenging experience physiologically and for some women psychologically (Affonso & Domino, 1984;De Schepper et al, 2016;Dekel, Ein-Dor, Dishy, & Mayopoulos, 2020;Orovou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The experience of childbirth has long been established to have a spectrum of potential impacts on the well-being of women, with potential negative impacts increasing clinical concern (Grandone et al, 2020;Harrison, Ayers, Quigley, Stein, & Alderdice, 2020;Peiris-John, Park, Wells, Kool, & Wise, 2020;Picetti et al, 2020;Watson, White, Hall, & Hewitt, 2020). Childbirth is a challenging experience physiologically and for some women psychologically (Affonso & Domino, 1984;De Schepper et al, 2016;Dekel, Ein-Dor, Dishy, & Mayopoulos, 2020;Orovou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the following article, Peiris‐John et al . step up to the challenge, identifying all audits undertaken in eight New Zealand public hospitals during 2005–2014, to determine whether women diagnosed with third‐ or fourth‐degree perineal tears were receiving the care recommended in their relevant guidelines 7 . These authors found considerable variations in the type of anaesthesia provided, intraoperative techniques, post‐operative care, outpatient care and referral for physiotherapy.…”
mentioning
confidence: 99%
“…In this issue of ANZJOG, Oh et al report on the experience, including training and frequency of exposure to cases, of colorectal surgeons across Australia and New Zealand 6. They find some important deficiencies in the management of OASI and recommend a multidisciplinary team involving both obstetricians and surgeons as the standard of care for these injuries.In the following article, Peiris-John et al step up to the challenge, identifying all audits undertaken in eight New Zealand public hospitals during 2005-2014, to determine whether women diagnosed with third-or fourth-degree perineal tears were receiving the care recommended in their relevant guidelines 7. These authors found considerable variations in the type of anaesthesia provided, intraoperative techniques, post-operative care, outpatient care and referral for physiotherapy.…”
mentioning
confidence: 99%